2021
DOI: 10.1097/md.0000000000025794
|View full text |Cite
|
Sign up to set email alerts
|

Application and side effects of blood flow restriction technique

Abstract: The physiological benefits of applying blood flow restriction (BFR) in isolation or in the presence of physical exercise have been widely documented in the scientific literature. Most investigations carried out under controlled laboratory conditions have found the technique to be safe. However, few studies have analyzed the use of the technique in clinical settings. To analyze how the BFR technique has been applied by professionals working in the clinical area and the prevalence of side effects (SEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The interest and adoption of blood flow restriction (BFR) training in the rehabilitation and fitness settings has increased substantially in recent years ( de Queiros et al, 2021 ; Mills et al, 2021 ; Cuffe et al, 2022 ). Fueled at least in part by its ability to generate musculoskeletal and cardiovascular performance benefits with reduced mechanical loads ( Lixandrão et al, 2018 ; Formiga et al, 2020 ), this interest has also fueled an in-kind response from the device manufacturing market.…”
Section: Introductionmentioning
confidence: 99%
“…The interest and adoption of blood flow restriction (BFR) training in the rehabilitation and fitness settings has increased substantially in recent years ( de Queiros et al, 2021 ; Mills et al, 2021 ; Cuffe et al, 2022 ). Fueled at least in part by its ability to generate musculoskeletal and cardiovascular performance benefits with reduced mechanical loads ( Lixandrão et al, 2018 ; Formiga et al, 2020 ), this interest has also fueled an in-kind response from the device manufacturing market.…”
Section: Introductionmentioning
confidence: 99%
“…Professionals reporting cases of subcutaneous hemorrhaging with BFRT stated that the subcutaneous hemorrhaging was transient and resolved quickly even if individuals continued their training session. 47 An effect that wasn't reported by Anderson and his colleagues but was reported to be seen by the cross-sectional study conducted by De Queiros and his associates was fainting. 47 Regarding witnessing individuals faint from BFRT, healthcare found fainting to be linked to the decrease in venous return induced by BFRT, which can cause a reduction in cardiac preload, which can lead to decreased blood flow to the brain.…”
Section: Adverse Eventsmentioning
confidence: 89%
“…44 From the studies analyzed, 1,672 people were reported to have an adverse event after undergoing BFRT out of 25,813 people. The most commonly reported adverse events that occurred in people that underwent BFRT were extremity tingling, delayed onset muscle soreness (DOMS), subcutaneous hemorrhaging, and rhabdomyolysis 44,47 In a cross-sectional study consisting of 113 professionals in the fields of physical rehabilitation and exercise science, the health professionals reported using BFRT on multiple age groups ranging from youth (≤18 years), young adults (20 to 29 years old), and older adults (60-80 years old). 47 The Health professionals within this study reported that only 3.5% of youth, 74.6% of young adults, and 30.7% of older adults they saw in their respective fields were subjected to BFRT.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations